Autorregulación y los efectos de una intervención educativa en secundaria - Rosa María Osés Bargas; Jorge Carlos Aguayo Chan; Efraín Duarte Briceño; Jorge Isaac Ortega (Revista Electrónica de Investigación Educativa)
The purpose of this paper was to foster the first grade students’ self-regulatory learning skills in a public elemental secondary school through an educational intervention program that allows them to acquire effective study skills to improve academic performance. The whole population of first grade (226) classified into six classrooms labeled from A to F was participated. The Flores and Cerino (2000) Self-regulation Questionnaire was used. It was an applied research with a time series design with static groups (Mertens, 2005). The outcomes show that the educational intervention program had an impact only on support and meta-cognitive factors in classroom A, and on the cognitive factor in classrooms A and D. In conclusion, it is important to point out the professors’ meaningful role in teaching these processes as well as the use of other methods to assess the development of the sel-regulation processes.